Validation of calcium (Ca) analysis in dolomite fertilizer using atomic absorption spectrophotometer (AAS) - Agustiyar, Fandika; Umar, Wakhid Khoirul; Guritno, Agung (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
The method of determining calcium (Ca) in dolomite fertilizer has been validated using atomic absorption spectrophotometer (AAS). Determining calcium (Ca) in dolomite fertilizer refers to the Indonesian National Standard (SNI) 02-2804-200. Based on the results of the calcium (Ca) test on dolomite fertilizer, the correlation coefficient (r) was 0.9949, and the % relative standard deviation (RSD) was 0.6472%, less than 2/3 CV Horwitz of 1.5963. The accuracy value is 100.30%, the precision value is 0.6471%, the detection limit for the LOD method is 0.2817, the LOQ is 0.9390, and the instrument detection limit is LOD 0.1159 and LOQ 0.3864. This study shows that the determination of calcium (Ca) in dolomite fertilizer using the SNI method using the Atomic Absorption Spectrophotometer (AAS) can be used with valid results.